Probiotic Supplementation during Pregnancy: Evaluating the Current Clinical Evidence against Gestational Diabetes Mellitus - Pavlidou, Eleni; Alexatou, Olga; Tsourouflis, Gerasimos; Antasouras, Georgios; Papadopoulou, Sousana K.; Papandreou, Dimitrios; Sampani, Anastasia; Giaginis, Constantinos (Current Diabetes Reviews, 2025)
BackgroundGestational diabetes mellitus (GDM) constitutes a common metabolic disorder that could lead to deleterious short- and long-term complications in both the mother and her infant. Probiotic supplementation seems to exert diverse, healthy effects by acting as a preventive agent against various human diseases, including GDM.ObjectiveThe purpose of the current narrative review was to critically summarize and scrutinize the available clinical studies during the last 15 years (2008-2023) concerning the use of probiotic supplementation during pregnancy as a protecting agent against GDM.MethodsA thorough and in-depth search was performed in the most accurate scientific databases, e.g., PubMed., Scopus, Web of Science, and Google Scholar applying effective, and relevant keywords.ResultsThere are currently some clinical studies suggesting the potential beneficial impact of probiotic supplementation in the prevention and/or co-treatment of GDM. Nevertheless, there is a high heterogeneity amongst the available clinical studies concerning the dosage, the administration duration, the probiotic species types, the method designs and protocols, and the study populations.ConclusionProbiotic supplementation at conventional dosages and in combination with a balanced healthy diet, and lifestyle seems to reduce the the risk of developing GDM, while ameliorating the severity of its symptoms. Further clinical studies taking into account the above considerations should be performed to establish conclusive results, while the future meta-analyses should include studies with the feasibly lowest heterogeneity.
Keywords: pregnancy